Resources Based Planning Framework for Infrastructure Maintenance and Rehabilitation Projects - Gad, Heba (AUC Knowledge Fountain, 2023)
Infrastructure maintenance and rehabilitation projects involve activities scattered over a large geographical area (e.g., scattered road segments maintenance, telecom towers maintenance program, etc.). Planning such projects require a resource-based approach that accounts for the implications of resource mobility between activities’ locations in terms of time & cost. Existing scheduling techniques fall short of addressing the unique challenges of the scattered nature of these projects in combination with organization's limited resources availability. To address this need, this research presents a resources-based planning framework for infrastructure maintenance and rehabilitation scattered projects with the objective of enhancing resources utilization achieving time and cost savings associated with the economy of scale of these projects. The proposed framework is applied through an agent based (AB) model using Anylogic software. The model includes several features: (1) adaptation of queuing theory in prioritizing & assigning resources to activities; (2) Integration of Multimode resources in combination with different construction methods for activities; and (3) GIS based analysis of resources mobility between activities. The research, also, discusses the application of the proposed framework in an agent based (AB) simulation model adapting to the complexity of real-life projects called Resource Based Scheduler (RBS) The model was applied on a case study and several examples from literature where it successfully developed resource deployment plans detailing resources mobility between activities, as well as the activity process itself and was able to develop a schedule 30% shorter than literature. The proposed framework enables efficient resources-based planning of scattered projects on a large scale as an added value for the planning of infrastructure maintenance & rehabilitation projects.